2008
DOI: 10.1016/j.jasms.2007.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of ginkgo flavonoids and terpenoids in plasma: Ammonium formate in LC mobile phase enhancing electrospray ionization efficiency and capacity

Abstract: Extracts from Ginkgo biloba leaves confer their therapeutic effects through the synergistic actions of flavonoid and terpenoid components. We herein describe the development of an LC-MS/MS-based method for simultaneous determination of flavonoids (quercetin, kaempferol, and isorhamnetin) and terpenoids (bilobalide, ginkgolides A, B, C, and J) in acid-hydrolyzed plasma by circumventing cross-interference between the flavonoids and terpenoids identified. Notably, inclusion of ammonium formate (0.2 mM) in the mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…According to the recent literature, the negative mode was suitable to ionize the seven components (Zhao et al, 2008;Wu et al, 2013). The instrument parameters were optimized to detect parent and daughter ions.…”
Section: Uplc-ms/ms Conditions and Sample Preparation Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the recent literature, the negative mode was suitable to ionize the seven components (Zhao et al, 2008;Wu et al, 2013). The instrument parameters were optimized to detect parent and daughter ions.…”
Section: Uplc-ms/ms Conditions and Sample Preparation Optimizationmentioning
confidence: 99%
“…This phenomenon may due to the co-eluting of residual matrix components interfering with the ionization of the target analyte (Dams et al, 2003). Zhao et al (2008) reported that inclusion of ammonium formate (0.2 mmol/L) in the mobile phase generated beneficial LC-electrolyte effects, including increased ESI efficiency and capacity. While 0.1% HCOOH in the mobile phase was found to improve the peak shape of the analytes, ammonium formate had no significant effect on the analytes in our study.…”
Section: Matrix Effect and Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous papers [10][11][12][13] have described high-performance liquid chromatography (HPLC) methods for the simultaneous determination of one or several flavonoids in plasma, but in these researches, administrated drug was single compound or mixture of several flavonoids, so these methods are not suitable for analysis of flavonoids in beagle dog plasma after being administrated GBE. Some scholars have published analysis method of Ginkgo flavonoids in dog or rabbit plasma by liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS) [14] or HPLC [15][16], but they only developed the simultaneous determination of quercetin, kaempferol, and isorhamnetin using acid hydrolysis or calculated total peak area of GBE in plasma. Except for quercetin, kaempferol, and isorhamnetin, some Ginkgo flavonoid glycosides, such as rutin and quercetrin, or other flavonols, such as myricetin, luteolin, genistein, and apigenin etc., are also active components of GBE, so it is essential to develop a method to determine both of them in plasma samples for the purpose of studying the mechanism of action through optimizing the extraction method and chromatographic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The findings are consistent with previously reports. Some researchers [15,16] considered that it might be caused by some factors, such as enterohepatic circulation [7,17], distribution of the drug in vivo, and so on. To clarity the reason of double peaks of QCT, KMF, and ISR, a study on the absorption mechanism was performed [15].…”
Section: Discussionmentioning
confidence: 99%